2013
DOI: 10.5194/isprsannals-ii-2-w1-43-2013
|View full text |Cite
|
Sign up to set email alerts
|

Complex Urban Simulations and Sustainable Urban Planning With Spatial and Social Implications

Abstract: ABSTRACT:Cities can be seen as complex systems of heterogeneous processes with a high variety of different influences (e.g. social, infrastructural, economic, and political impacts). This especially applies for tasks concerning urban development of existing assets. The optimization of traffic flows, reduction of emissions, improvement of energy efficiency, but also urban climate and landscape planning issues require the involvement of many different actors, balancing different perspectives, and divergent claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Given the complexity of urban residential settlement development, appropriate management of such a system requires knowledge of its boundaries, resources, interactions, surroundings, and thresholds [28,29]. No specific level (e.g., city, neighborhood and building) could stand alone; rather, each of them must be considered as a part of a broad urban system [30]. Therefore, a clear multidimensional system approach is essential for contributing to further urban development.…”
Section: Background Of Energy-optimized Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of urban residential settlement development, appropriate management of such a system requires knowledge of its boundaries, resources, interactions, surroundings, and thresholds [28,29]. No specific level (e.g., city, neighborhood and building) could stand alone; rather, each of them must be considered as a part of a broad urban system [30]. Therefore, a clear multidimensional system approach is essential for contributing to further urban development.…”
Section: Background Of Energy-optimized Urban Planningmentioning
confidence: 99%
“…The emerging complexity of urban systems has already indicated that the interdisciplinary efforts are necessary, along with early integration of stakeholder's participation in decision-making at every level and scale [3,30]. After a critical review of 58 pilot cities, the EU [50] noted that "An integrated urban planning process should involve significant experts of various urban departments from the very beginning".…”
Section: Conceptual Framework: the "Enup" Modelmentioning
confidence: 99%